PERENCANAAN LAYOUT GALANGAN KAPAL DI POLITEKNIK NEGERI MADURA MENGGUNAKAN ALGORITMA CORELAP - Muhammad Musta'in; Heni Siswanti; Anauta Lungiding Angga R; Arifah Amanatul Rohmah (Politeknik Negeri Madura, 2020)
As a campus that has a maritime mission, Madura State Polytechnic has made a master plan for campus development by building a shipyard. This is also supported by the campus located on the beach. In preparing the shipyard, facilities are very important, so a careful planning is needed in doing the layout. In this paper, we will propose a layout process based on the production flow pattern of shipbuilding, comparison with the layout design using the CORELAP algorithm method, by calculating the percentage value of material handling and planning tools and facilities for the POLTERA shipyard. The facility layout planning obtained new and repaired building types with an area of ??5.16 hectares and a layout design with an L layout production flow pattern. The design had a material handling percentage value of 21.62%.